Dry wear behavior of Brass alloy before and after Nickel deposition treatment (Journal of the College of Basic Education, 2022)
Impact of electroplating affidavit of Nickel, treatment on mechanical properties, wear safety, and Vickers hardness of Brass alloy were studied. The examples were dealt with by utilizing electroplating testimony of Nickel on Brass surface specimens . The wear conduct of the samples were considered for all samples prior and then afterward treatment by Nickel statement and the dry wear tests were done by utilizing stick on-plate procedure. The samples were machined as a plate with width of 30 mm and. All samples were led by Scanning Electron Microscopy (SEM), Energy-Dispersive Spectrometry examination (EDS), optical microscopy, and Vickers hardness. The results demonstrated that the dry wear rate were diminished after Nickel affidavit and expanded Vickers hardness values by proportion of 2: 4 : 1. The results demonstrated that the estimations of wear rate for samples having electroplating affidavit of nickel are short of what specimens without deposition